Potential of Thibbun Nabawi Habbatusauda (Nigella sativa); Review of the Active Pharmacological Timoquinone - Mardan, Mardan; Ismail, Isriany; Rauf, Afrisusnawati (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2021)
Habbatusauda or Black Seed or Black Cumin (Nigella sativa) has been widely mentioned in various Islamic studies, including its potential as a "cure for all diseases except death. The hadith can be interpreted as improving immunity and enhancing memory (physical and cognitive aspects). Scientifically, the high content of thymoquinone and DHA in Black Seed plays a major role as an immunomodulator and brain nutrition. Black Seed contains both hydrophilic and lipophilic compounds. Amino acids, proteins, carbohydrates, essential oils, fixed oils, sterols, alkaloids, saponins and crude fiber, and minerals, thymoquinone, p-cymene, longifoline thujene, carvacrol, cubebene, pinene, limonene, pinene, sabinene are the ingredients. Timoquinone is present at a concentration of 3.5-8.7 mg/g in oil. Black Seed Oil is also high in DHA (3%). The content of the active compound Timoquinone is most responsible for its wide range of effects.